The Value of Compassion in Indonesian Poems - Angger Gilang Praditama; Suroso (Widyantara, 2023)
This study aims to describe the form of affection contained in Indonesian poetry. This research is a qualitative descriptive study. The data in this study are in the form of quotations of words, phrases, or sentences from Joko Pinurbo's collection of Surat Kopi poems about affection. The data source is a collection of poetry from Surat Kopi by Joko Pinurbo. Data obtained by reading notes technique. Data were analyzed with interactive analysis techniques. The results of the study show, first, the forms of affection contained in the poetry collection Surat Kopi by Joko Pinurbo are love for God, erotic love, and motherly love. Love for God is found in the form of God who is the Most Giving, the Most Merciful, God who gives His love to all human beings, God is a place to complain about anxiety. Erotic love contained in this collection of poems is a person's sincerity in loving his lover. Maternal love contained in this poetry collection is in the form of a mother who always prays for her child, strong feelings from a mother, immeasurable mother's love, a mother's sacrifice, a mother who is an example for her children, and a mother who is the source of all love.